Weighted Gene Co-expression Network Analysis Identifies CALD1 as a Biomarker Related to M2 Macrophages Infiltration in Stage III and IV Mismatch Repair-Proficient Colorectal Carcinoma - Zheng, Hang; Bai, Yuge; Wang, Jingui; Chen, Shanwen; Zhang, Junling; Zhu, Jing; Liu, Yucun; Wang, Xin (Frontiers in Molecular Biosciences, 2021)
Immunotherapy has achieved efficacy for advanced colorectal cancer (CRC) patients with mismatch-repair-deficient (dMMR) subtype. However, little immunotherapy efficacy was observed in patients with mismatch repair-proficient (pMMR), hence identifying new immune therapeutic targets is imperative for those patients. In this study, the transcriptome data of stage III/IV CRC patients were retrieved from Gene Expression Omnibus database. CIBERSORT algorithm was used to quantify immune cellular compositions, and results revealed that M2 macrophages fractions were higher in pMMR patients as compared with dMMR subtype, and pMMR patients with higher M2 macrophages fractions experienced shorter overall survival (OS). Subsequently, weighted gene co-expression network analysis and protein-protein interactions network analysis identified six hub genes related to M2 macrophages infiltrations in pMMR CRC patients: CALD1, COL6A1, COL1A2, TIMP3, DCN and SPARC. Univariate and multivariate Cox regression analysis then determined CALD1 as the independent prognostic biomarker for OS. CALD1 was upregulated specifically in CMS4 CRC subtype, and single-sample Gene Set Enrichment Analysis (ssGSEA) revealed CALD1 was significantly correlated with angiogenesis and TGF-β signaling gene sets enrichment scores in stage III/IV pMMR CRC samples. ESTIMATE algorithm and correlation analysis revealed that CALD1 was significantly associated with multiple immune and stromal components in tumor microenvironment. In addition, GSEA demonstrated that high expression of CALD1 was significantly correlated with antigen processing and presentation, chemokine signaling, leukocyte transendothelial migration, vascular smooth muscle contraction, cytokine-cytokine receptor interaction, cell adhesion molecules, focal adhesion, MAPK and TGF-beta signaling pathways. Furthermore, the proliferation, invasion and migration abilities of cancer cells were suppressed after reducing CALD1 expression in CRC cell lines. Taken together, multiple bioinformatics analysis and cell‐level assays demonstrated that CALD1 could serve as a prognostic biomarker and prospective therapeutic target for stage III/IV pMMR CRCs.